Analisis Hubungan Keaktifan Ibu dalam Posyandu dengan Penurunan Jumlah Balita Bawah Garis Merah - Putri Handayani Setyaningsih; Lira Kurnia (STIKes Kharisma Persada, 2020)
Based on the results of the Basic Health Research (Riskesda) of the Ministry of Health in 2018, it showed that 17.7% of infants in Indonesia with children under the age of five years were still experiencing nutritional problems. This figure consists of toddlers who experience malnutrition by 3.9% and those suffering from malnutrition by 13.8%. The purpose of this study was to determine the relationship of maternal activity in Posyandu with a decrease in the number of toddlers in the red line in the area of North Larangan Health Center in Tangerang City. The study used a descriptive correlation research with a cross sectional approach. The technique used in this study is stratified random sampling. Data collection was done by observing KMS toddler books, observations made were non-participant observations. The results of this study note that there is no significant relationship between maternal activity in Posyandu and a decrease in the number of toddlers under the red line in the North Larangan Health Center in Tangerang City. The results of active mothers were 63 respondents (70.0%). There is no relationship with the activity of mothers in reducing the number of children under five in the red line in the Posyandu area of the North Larangan Health Center in Tangerang City. It is recommended for Health Institutions to be able to improve the quality of services in conducting counseling, health promotion and services in order to prevent the occurrence of malnutrition status in infants.